Conspiracies Gone Wild: A Psychiatric Perspective on Conspiracy Theory Belief, Mental Illness, and the Potential for Lone Actor Ideological Violence - Pierre, Joseph (Terrorism and political violence, 2025)
Conspiracy theory belief (CTB) has been increasingly recognized as a driving force of extremist violence. This paper provides a psychiatric perspective on the phenomenon of CTB-driven violence in an effort to bridge the gap between psychiatry and terrorism studies. First, it makes a case for the growing relevance of CTB to ideologically-motivated violence and lone actor violence in particular. Next, acknowledging common themes of shadowy forces, clandestine plots, and malevolent motives, it argues that CTB can be reliably disentangled from delusional belief and examines the association between mental illness and terrorism with a critical and skeptical eye. Finally, after reviewing the association between CTB and terrorist radicalization within existing models from psychiatry and terrorism studies, it outlines five stages of ideological commitment to characterize the link between CTB and the perpetration of ideological violence. Rather than alternately “explaining” terrorism on the basis of mental illness or “blaming” it on ideological extremism depending on biased attributions, modeling ideological commitment through a normalizing cognitive and socio-epistemic framework can facilitate a less stigmatizing understanding of the link between CTB and ideologically-motivated violence.